2013
DOI: 10.1111/lam.12024
|View full text |Cite
|
Sign up to set email alerts
|

Indoor dust and air concentrations of endotoxin in urban and rural environments

Abstract: Significance and Impact of the Study: Rural dairy farming is associated with high exposure to indoor endotoxins as compared to rural nonfarming houses and urban houses. The time spent on the mattress (7 h for an adult) and of the proximity of the contaminated source should be taken into account with the other causes of exposure. AbstractStudies in European children from a farming background have shown that these children have a reduced risk of asthma and atopic sensitization compared to their urban counterpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
(109 reference statements)
0
37
1
1
Order By: Relevance
“…This finding is similar to those of previous longitudinal studies for eczema 28 and asthma, 29 but to our knowledge, this is the first study to prospectively examine this relationship for the development of food allergy. Previous studies have demonstrated that endotoxin levels are lower in urban environments than in rural farming areas, 30,31 and a recent study examining the indoor microbiome in the same URECA cohort found that exposure to specific allergens and bacteria was associated with reduced sensitization to inhalant allergens as well as recurrent wheeze (in press). Therefore, while it has been previously suggested that the high rates of allergy and asthma in the inner city contradict the hygiene hypothesis, 32 both of these studies suggest that this is not actually the case.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is similar to those of previous longitudinal studies for eczema 28 and asthma, 29 but to our knowledge, this is the first study to prospectively examine this relationship for the development of food allergy. Previous studies have demonstrated that endotoxin levels are lower in urban environments than in rural farming areas, 30,31 and a recent study examining the indoor microbiome in the same URECA cohort found that exposure to specific allergens and bacteria was associated with reduced sensitization to inhalant allergens as well as recurrent wheeze (in press). Therefore, while it has been previously suggested that the high rates of allergy and asthma in the inner city contradict the hygiene hypothesis, 32 both of these studies suggest that this is not actually the case.…”
Section: Discussionmentioning
confidence: 98%
“…We could only compare the concentrations found in our study with other studies conducted in children's homes. Significant differences between urban and rural environment were noticed [39]. It therefore seems that endotoxins concentrations demonstrated by us are too low to protect children in the way defined in the "hygienic hypothesis".…”
Section: Analysis Of (1→3)-β-d-glucansmentioning
confidence: 92%
“…If this is the case, these findings strongly suggest that silica exposure deteriorates phagocytic ability of alveolar macrophages against foreign matter and consequently elevates bioactive LPS concentration in the lung, because LPS is ubiquitous in the environment: LPS is part of the outer membrane of the cell wall of Gram-negative bacteria (Heine et al, 2001), such as Escherichia coli (E. coli), Salmonella, Shigella, Pseudomonas and Neisseria, and thus LPS molecules are present in the air of laboratory animal rooms (Kaliste et al, 2002(Kaliste et al, , 2004Ooms et al, 2008) and in indoor air (Bouillard et al, 2005;Larsson et al, 2004;Sebastian et al, 2006;Simpson et al, 1999). In addition, multiple studies show that measurable amount of endotoxin exists in house dust (Barnig et al, 2013;Gehring et al, 2002;Gereda et al, 2001;Holst et al, 2015;Jacobs et al, 2013;Ownby et al, 2013;Park et al, 2001), which is presumed to exacerbate asthma (Kanchongkittiphon et al, 2015). Accordingly, it is highly likely that exposure to a-quartz deteriorates the phagocytic ability of M2 macrophages, which results in the elevation of bioactive LPS concentration in the lung.…”
Section: Possible Elevation Of Lps Concentration In the Lung By A-quartzmentioning
confidence: 97%